Imaging Features of Postradiotherapy Changes in Head and Neck Cancers - Gehani, Anisha; Sen, Saugata; Chatterjee, Sanjoy; Mukhopadhyay, Sumit (Indian Journal of Radiology and Imaging, 2021)
Radiation therapy is the mainstay in the treatment of head and neck cancers, in addition to surgery and chemotherapy. Expected radiotherapy changes evolving over time may be confused with recurrent tumor. Conversely, even residual or recurrent tumor in the setting of postradiotherapy changes may be difficult to identify clinically or even by radiological imaging. Therefore, it is important to be familiar with the temporal evolution of these changes. The purpose of this pictorial essay is thus to illustrate distinctly the expected radiotherapy changes and radiotherapy-related complications in the head and neck region and to differentiate them from tumor recurrence on routine cross-sectional imaging techniques (computed tomography and magnetic resonance imaging).
Keywords: postradiotherapy changes; head and neck malignancy; head and neck squamous cell carcinoma; radiation complications